Implementasi Model Pembelajaran Matematika Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Wordwall untuk Meningkatkan Hasil Belajar Peserta Didik di SMA Negeri 9 Surabaya - Aulia Yusrika Qurrotu’ain; Anik Kirana; Fitria Indahwati (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study was conducted by looking at the low learning outcomes of class X-2 students at SMA Negeri 9 Surabaya in the previous material, namely SPLTV. This study was conducted with the aim of improving students' mathematics learning outcomes in the quadratic equation material by implementing a cooperative learning model of the team games tournament (TGT) type using the help of wordwall. This study is included in classroom action research which is carried out in two cycles. The subjects of the study used were 36 class X-2 students at SMA Negeri 9 Surabaya. The research data were obtained through pretest, observation, and posttest. The analysis data from the pretest and posttest results were in the form of quantitative data which would be used to determine the increase in student learning outcomes. While the analysis data from the observation results in the form of qualitative data were used as a guideline to improve and perfect learning activities from cycle I to cycle II. Based on the results of the study that has been carried out, it shows that implementing a cooperative learning model of the team games tournament (TGT) type using the help of wordwall on the quadratic equation material can improve the learning outcomes of class X-2 students at SMA Negeri 9 Surabaya. The classical completeness of the pretest cycle I was 44.4%. After the implementation of the TGT type cooperative learning model, there was an increase to 77.8% in the posttest of cycle I. In cycle II, it increased again to 94.6% with a classical completion target of 85%.